Competitive interactions across a soil fertility gradient in a multispecies forest. (7th March 2013) - Coates, K. David; Lilles, Erica B.; Astrup, Rasmus; Kitzberger, Thomas
Summary Whether plant competition grows stronger or weaker across a soil fertility gradient is an area of great debate in plant ecology. We examined the effects of competition and soil fertility and their interaction on growth rates of the four dominant tree species in the sub‐boreal spruce forest of British Columbia. We tested separate soil nutrient and moisture indices and found much stronger support for models that included the nutrient index as a measure of soil fertility. Competition, soil fertility and their interaction affected radial growth rates for all species. Each species supported a different alternate hypothesis for how competitive interactions changed with soil fertility and whether competition intensity was stronger or weaker overall as soil fertility increased depended on the context, specifically, species, neighbourhood composition and type of competition (shading vs. crowding). The four species varied slightly in their growth response to soil fertility. Individual species had some large variations in the shapes of their negative relationships between shading, crowding and tree growth, with one species experiencing no net negative effects of crowding at low soil fertility. Goodness‐of‐fit was not substantially increased by models including competition–soil fertility interactions for any species. Tree size, soil fertility, shading and crowding predicted most of the variation in tree growth rates in the sub‐boreal spruce forest. Synthesis. The intensity of competition among trees across a fertility gradient was species‐ and context‐specific and more complicated than that predicted by any one of the dominant existing theories in plant ecology.